Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


Since a point(x,y) is given, A (2,3),....substitute x=2 and y=3 in the equation y=x^2-6x+c… so 3=(2)^2-6(2)+c.... 3=4-12+c.... 3-4+12=c... 11=c.... Therefore, the unknown (c) is equal to 11.
0 0 0
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts